The socio-legal status and pictorial representations of children and adolescents in early modern Ottoman society - İlhan, Zehra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This thesis aims to make an art historical examination of early modern children and adolescents in Ottoman book paintings that were produced from the sixteenth to the beginning of the eighteenth century. This thesis has two main focuses. The first one is to examine what childhood and adolescence were and meant for the early modern Ottomans through various literary sources derived primarily from the elite culture, and to demonstrate that the perception of childhood and adolescents depended on gender, class and age. Secondly, it attempts to illuminate the artistic conventions of representations of children and adolescents by exploring the book paintings in connection to the socio-legal and cultural dynamics of the early modern Ottoman society.
Keywords: Turkey -- History -- Ottoman Empire -- 16th century.; Turkey -- History -- Ottoman Empire -- 18th century.; Picture books for children -- History and criticism.